Collaboration avec des Maisons d’édition à l’élaboration de Manuels - Araujo Portugal, Juan Carlos (Íkala, Revista de Lenguaje y Cultura, 2015)
The coursebook is still a pivotal component in any foreign language course, even though it may be complemented with the use of the new technologies. As students’ needs keep changing all the time, and schools as well as teachers have to meet them, publishers try to obtain first hand information about them. Apart from this, publishers also try to establish whether their responses by means of the new methods they launch onto the market really satisfy these needs. To do so, they seek language teachers’ cooperation, which adopts different ways– classroom observation, exchanging opinions with teachers, piloting specific units from a new method, considering or assessing particular aspects that the publishers are interested in, revising a new method. This paper illustrates the experience of a teacher of English at a Escuela Oficial de Idiomas in Spain (a state language school in Spain, one of the authorised institutions in Spain for the teaching of foreign languages), who has collaborated with various publishers in different ways. His experience may act as a stimulus for other language teachers who may decide to take part in other projects in the future if they have the chance to do so.